COMPARATIVE STUDY OF THINK-PAIR-SHARE TECHNIQUE ANDSMALL GROUP DISCUSSION TECHNIQUE IN WRITING DESCRIPTIVE TEXT - Erika, Helda Julia (Inspiratif Pendidikan, 2022)
The objective of this research wasto find out whether there is a significant difference of the students’writing achievement after implementing Think-Pair-Share and Small Group Discussion techniques. This research used quantitative approach and the population of this research was two classes of the tenthgrade students of SMA YP Unila Bandar Lampung. The instrument was writing test and the data was analyzed through independent sample t-test. The result indicated that there was a significant difference of the student’s reading achievement after implementingthink-pair-share and small group discussiontechniques which can be seen from the value of the sig level is lower than 0.05 (0.000<0.05). Then, small group discussion is more effective than think-pair-share technique in teaching writing because the mean score in small group discussion class is higher than mean score in think-pair-share class (39.2963 > 18.9375).